2021
DOI: 10.1002/zoo.21610
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific actuarial and reproductive senescence in zoo‐housed tiger (Panthera tigris): The importance of sub‐species for conservation

Abstract: A fifth of all known species are currently classified as threatened in the wild: the rate of biodiversity loss is rapid, continuous, and mostly due to anthropogenic activities. To slow down this decline, the accurate estimation of demographic parameters for threatened species is critical. With this aim, zoo institutions play an important role, giving access to data on zoo-housed animals, which aids researchers working on species life-history traits and intrinsic factors influencing the fitness of both sexes, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…living under human care have a much longer life expectancy relative to their free-ranging counterparts. 28,45 For example, longevity in zoo-housed tigers is approximately 19 years while a study on wild Amur tigers demonstrated a maximum lifespan of 7 years in females and even less in males. 10 Environment and husbandry have also been implicated in the development of degenerative lesions, particularly the use of concrete or other hard flooring and raised platforms.…”
Section: Discussionmentioning
confidence: 99%
“…living under human care have a much longer life expectancy relative to their free-ranging counterparts. 28,45 For example, longevity in zoo-housed tigers is approximately 19 years while a study on wild Amur tigers demonstrated a maximum lifespan of 7 years in females and even less in males. 10 Environment and husbandry have also been implicated in the development of degenerative lesions, particularly the use of concrete or other hard flooring and raised platforms.…”
Section: Discussionmentioning
confidence: 99%
“…The studbook data collected to facilitate cooperative management provides valuable life history information for a wide range of taxa, which informs the husbandry practices for ex situ populations. For example, these data are used to estimate lifespans, reproductive potential and fertility, clutch or litter sizes, and the impacts of inbreeding depression (Franklin et al, 2021;Tidière et al, 2016Tidière et al, , 2017Tidière et al, , 2018Tidière et al, , 2021Trask et al, 2021). Data collected on zoo and aquarium populations also inform the management of in situ populations, for which detailed life history data often are lacking, and contribute to a greater scientific knowledge of not only the species data are collected for, but also their close relatives (Conde et al, 2019;Galla et al, 2021;Medici & Desbiez, 2012;Princée, 2016).…”
Section: Benefits Of Science-based Management and Recommendations For...mentioning
confidence: 99%
“…At present, six extant tiger subspecies have been proved through whole-genome sequencing analyses from 32 voucher specimens [2] by Liu et al [3] and Sun et al [4]. Tidière et al [5] revealed that the six subspecies presented different reproductive and survival patterns. Among the six subspecies, the Sumatran tiger is the only island population with significant genetic distances from all continental tigers [6] and the South China tiger is the rarest tiger subspecies (https://www.iucnredlist.org) (accessed on 15 December 2021).…”
Section: Introductionmentioning
confidence: 99%